Some Aspects of Bamboo Inventory - Tomar, M. S. (Indian Forester, 1974)
At present, data is not available to know the bamboo resources of the country correctly. A proper bamboo inventory is much needed to give the information of its area, total growing stock and annual yield. Bamboo inventory has its own problems and peculiarities. These are to be taken care of to arrive at a correct assessment. Bamboo area is defined and classfied according to its condition, stocklng, species, quality, etc. Clumps and culms are also classified into various categories. The area is then mapped with the help of aerial photography. The data collected is analysed. To achieve this objective, a separate organization for survey of bamboo and other minor products is necessary.